On the conveyor belt of public employment programs between 2009 and 2013 in Hajdúböszörmény - Oláh, Judit; Szabó, Andrea (Applied Studies in Agribusiness and Commerce, 2014)
Present study focuses on the national and European popularity of public employment programs within the Active Labour Market Policies (ALMP) between 2009 and 2013, and emphasizes the lack of their transitive effects by two national empirical researches. It is a crucial question at either the governmental level or the local level or even at the level of the people that after the participation whether the supported employees can find a job, whether the programs have transitive effects or the possibility of re-employment is greater. 50% one-time participation defined in the first hypothesis was examined in two empirical studies. In the first case this ratio was verified neither in input sampling (45,6%) nor in output sampling (40,83%). In case of the sampling in 2013 it was successful (78%). In Hajdúböszörmény revealing the situation of the labour market we concluded that practically people after the supported employment have minimal chance to find a job, there are still negative tendencies in the primary market, and local government tries to struggle with the price by utilizing public employment as a single tool. The two empirical sampling drew the attention that the lower the transitive effects of the examined programs are, the stronger the phenomenon of locking-in and rotating is.